The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.bbr.2015.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms of predatory aggression in rats—Implications for abnormal intraspecific aggression

Abstract: Our recent studies showed that brain areas that are activated in a model of escalated aggression overlap with those that promote predatory aggression in cats. This finding raised the interesting possibility that the brain mechanisms that control certain types of abnormal aggression include those involved in predation. However, the mechanisms of predatory aggression are poorly known in rats, a species that is in many respects different from cats. To get more insights into such mechanisms, here we studied the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 53 publications
(104 reference statements)
1
26
0
Order By: Relevance
“…Finally, Golden et al (2019) indicate that the NAc shell may be more important than the NAc core in the mediation of appetitive aggression. This aligns with previous literature showing that the NAc shell receives inputs from the VTA and projects to the lateral hypothalamus (LH), a region commonly implicated in aggression (Tulogdi et al, 2015). The differential activation between the NAc shell and core is of particular interest because the NAc shell has been previously shown to have a role in formulating the value of reward, whereas the NAc core was associated with motivation to overcome response costs (West and Carelli, 2016).…”
Section: Review Ofsupporting
confidence: 88%
See 1 more Smart Citation
“…Finally, Golden et al (2019) indicate that the NAc shell may be more important than the NAc core in the mediation of appetitive aggression. This aligns with previous literature showing that the NAc shell receives inputs from the VTA and projects to the lateral hypothalamus (LH), a region commonly implicated in aggression (Tulogdi et al, 2015). The differential activation between the NAc shell and core is of particular interest because the NAc shell has been previously shown to have a role in formulating the value of reward, whereas the NAc core was associated with motivation to overcome response costs (West and Carelli, 2016).…”
Section: Review Ofsupporting
confidence: 88%
“…The LH has been previously associated with predatory aggression in rats and cats, and the VMH has been identified as key in the generation of attack behavior. (Tulogdi et al, 2015). The LH receives axon projections from multiple nuclei that have roles relating to appetitive aggression including the arcuate nucleus and the central amygdala.…”
Section: Review Ofmentioning
confidence: 99%
“…Tulogdi et al (59) found that both feeding attacks and proactive aggression were associated with innervation of the central and basolateral amygdala, the lateral hypothalamus, and the ventrolateral periaqueductal gray. By contrast, reactive aggression among rats was associated with the medial amygdala, the mediobasal hypothalamus, and the dorsal periaqueductal gray (59,60,62). These differences in rat innervation between proactive and reactive aggression were the same as those found in cats between quiet biting attacks and affective defensive behavior.…”
Section: Proactive Vs Reactive Aggressionmentioning
confidence: 78%
“…The results of Tulogdi et al (59,60) indicate the existence of two different pathways in a key neural circuit underlying aggression. They thereby conform to much other evidence of differential innervation for the two types of aggression in humans.…”
Section: Proactive Vs Reactive Aggressionmentioning
confidence: 99%
See 1 more Smart Citation